2005
DOI: 10.1038/sj.cgt.7700845
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficiency and specificity of ovarian cancer gene therapy in rats with a novel nonviral gene delivery system (GE7) via intraovarian artery perfusion approach

Abstract: Transfer of the herpes simplex virus type I-thymidine kinase gene, followed by the administration of ganciclovir (HSV 1 -tk/GCV) into ovarian cancer-derived cell line either in vitro or transplanted into nude mice has been shown to provide a potential strategy for the gene therapy of ovarian cancer. We investigated the antitumor effects of HSV 1 -tk/GCV strategy with a chemically induced rat ovarian cancer model and a tumor-selective gene delivery by a novel nonviral gene delivery system (GE7) through the ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…One interesting observation in this study is that there were many more tumor cells in the S-phase of the cell cycle in the PB/TK group than the control groups. We also observed similar results in a previous study involving ovarian cancer (31). This suggested that the HSV-tk/GCV system combined with S-phase targeted chemotherapy may enhance suicide gene therapy in cancer.…”
Section: Discussionsupporting
confidence: 89%
“…One interesting observation in this study is that there were many more tumor cells in the S-phase of the cell cycle in the PB/TK group than the control groups. We also observed similar results in a previous study involving ovarian cancer (31). This suggested that the HSV-tk/GCV system combined with S-phase targeted chemotherapy may enhance suicide gene therapy in cancer.…”
Section: Discussionsupporting
confidence: 89%
“…This same group also noted the importance of protecting siRNA through a vector in order to circumvent complete degradation of naked siRNA following intraperitoneal injection [21]. A novel nonviral gene delivery system, GE7, was recently reported by Jiang et al [22] to effectively transfer HSV1-tk (herpes simplex virus thymidine kinase) genes administered through ovarian arteries in rats with ovarian transplants. This system was much more effective than venous administration of the same construct.…”
Section: Nonviral Vectorsmentioning
confidence: 96%